Regenerating Regeneration: augmented reality and new models of minor architectural heritage reuse - Adolfo F.L. Baratta; Fabrizio Finucci; Antonio Magarò (Vitruvio: International Journal of Architectural Technology and Sustainability)
The paper presents the first results of an interdisciplinary research conducted by the Department of Architecture of Roma Tre University aimed at developing guidelines for enhancement of minor architectural heritage, urban  and suburban. The research evaluates the creation of a widespread museum that exploit cultural dissemination technologies in augmented reality. The economic crisis, not yet overcome, leads to rethink urban development and heritage conservation, reorienting design towards techniques and practices of reuse. These strategies represent one of the most effective ways to enhance and protect the minor architectural heritage, often protagonist of degradation and abandonment. It seems necessary that the architectural heritage protection has been articulated through contemporaneity, adapting itself to the age of Information Communication Technology. In addition to the architectural heritage, strictly intended as a monument, Italy has a complex system of goods well explained, in the broadest sense, as "minor architectural heritage ". This approach makes possible to identify the Italian Historical Cities as a new category of widespread heritage to be protected. Consequently, it emerges the need to put aside the discretization in punctual assets, approaching an entire system of architectural goods, characterized by a high degree of complexity. Valuing the latter in a sustainable way also passes through new technologies as augmented reality.